Implementasi Formulasi Grafik Raygor Dalam Uji Perbandingan Tingkat Keterbacaan Buku Ajar Bahasa Indonesia Kelas IX - Dimas Hermawan; Muhamad Rizki Nur Amin; Shafwan Raihan Farras; Ai Siti Nurjamilah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Textbooks are one of the central learning tools in achieving a predetermined level of competency. One of the main aspects of a good textbook is the suitability of its readability level to the level of cognitive development of students. This research aims to determine the readability level of the Class IX Indonesian Language Textbook, 2013 Curriculum Edition and the Merdeka Curriculum based on the Raygor Graphic formulation. The research method used was qualitative, with 5 text samples from each book edition. The research results showed that all text samples in both editions of the book had a readability level that did not match the cognitive level of class IX students. This is because all text samples have too many difficult sentences and words, so the text needs to be simplified. More than that, it is hoped that the results of this research can provide advice to textbook authors to pay more careful attention to readability aspects before inserting texts into textbooks. This is to ensure that the texts presented in textbooks are appropriate to the cognitive level and reading abilities of students at their grade level.